Variation in seed properties and germination capabilities among populations of the invasive weed Parthenium hysterophorus L. (Asteraceae) - Malka, Sahar; Eizenberg, Hanan; Matzrafi, Maor (Frontiers in Plant Science, 2023)
Parthenium hysterophorus (Asteraceae) is an invasive weed species that has invaded over 50 countries worldwide. It was first detected in 1980 at Tirat-Zvi, in eastern-northern Israel. In recent years, there has been an increasing concern over the spread of this weed in agricultural and non-agricultural habitats across the country. However, very little is known about the biology of P. hysterophorus and its variation among populations. Seeds collected from five locations across Israel were germinated and plants were grown in pollen-proof cages under uniform conditions to produce the progeny populations. Seeds originating from field populations were significantly smaller and lighter than seeds of the progeny populations. Germination occurred in the range of 10℃ to 30℃ (𝑇 𝑜 ranges from 19℃ to 22.3℃, 𝑇 𝑏 ranged from 9℃ to 15℃, 𝑇 𝑐 ranged from 24℃ to 30.5℃), depending on generation and population. A water potential-based model was developed to estimate germination under different soil water content using specific parameters (𝑏-slope, 𝑑upper limit, 𝑒infliction point). The model suggests a correlation between germination and water potential. Indeed, reduced germination was recorded for the lower water potentials especially for the progeny populations. We identified differences in seed size and weight, germination under different temperatures, and osmotic potential among P. hysterophorus Israeli populations.Differences across generations may arise due to the transgenerational effects. Our results, may shed light on the germination abilities of P. hysterophorus populations and provide vital insight into understanding the invasive capabilities of this highly noxious weed.